Alexander the Great in Mesopotamia in 331 BCE. (2022) - Marciak, Michał; Sobiech, Marcin; Pirowski, Tomasz
Abstract: This paper presents a selected aspect of research conducted within the Gaugamela Project, which seeks to finally identify the location of the Battle of Gaugamela. Its particular aim is to analyse the strategic situation of the army of Alexander the Great in Mesopotamia in the summer of 331 BCE, with a special focus on the itinerary and chronology of the army's march. The paper critically reviews Classical sources (Arrian, Curtius, Diodorus, and Plutarch), but also employs topographic and archaeological data as well as GIS capabilities ( least cost paths ). In contrast to most previous scholarship, it is suggested that the Macedonian troops crossed the Euphrates much later than suggested by Arrian ( Anab . 3.7.1) – around September 2, 331 BCE. Their march led across the Tur Abdin escarpment (via Nisibis) and left Mesopotamia through a ford in the vicinity of modern Cizre or Basorin. What is more, the Macedonian marching rate was definitely not slow ( contra W. E. Marsden), but faster than average due to the activity of the Persian scouting troops and logistic necessity. In total, the Macedonians covered around 370 to 394 km within a maximum of 16 days.